The inclusion of delirium in version 2 of the National Early Warning Score will substantially increase the alerts for escalating levels of care: findings from a retrospective database study of emergency medical admissions in two hospitals. Issue 2 (2019) - Mohammed, Mohammed A; Faisal, Muhammad; Richardson, Donald; Scally, Andy; Howes, Robin; Beatson, Kevin
No abstract available